The performance of Bursa Malaysia and its causality effect with South Korea, Taiwan and Japan stock exchanges : 2000 - 2004 / Omar Samat, Zuraidah Ismail and Jaslin Md Dahlan - Samat, Omar; Ismail, Zuraidah; Md Dahlan, Jaslin (Institute of Research, Development and Commercialization (IRDC), 2006)
This study examines the effect of returns from South Korea, Taiwan and Japan Stock Exchanges on the Bursa Malaysia in the year 2000 to 2004. The return from an individual stock exchange is no longer exclusive but with effect of globalization, it is also influenced by activities happening in other countries. The sources ofco-movements between stock markets are of great importance both for international investors and academics. A better knowledge of the underlying factors may improve portfolio management and help to assess the degree offinancial integration and efficiency.